Kratos’ Fathering in God of War (2018) - Jeremy Jordan (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
God of War (2018) tells the story of Kratos’ struggle to raise his son, Atreus, by himself because of his wife's passing. Using the Good Fathering theory by Morman & Floyd, Kratos fathering will be compared to the theory to determine whether he is a bad father or a good father. The top four characteristics to determine his fathering are love, role model, availability, and involvement. The study was done using a descriptive qualitative approach. The data analysis revealed that Kratos was a bad father in the early part of the game, but later he shows changes in four characteristics of good fathering through his actions in the middle of the story.